2016
DOI: 10.1158/0008-5472.can-15-1758
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activation of ERα by Estrogen and Prolactin in Breast Cancer Cells Requires Tyrosyl Phosphorylation of PAK1

Abstract: Serine/threonine kinase PAK1 is activated by estrogen and plays an important role in breast cancer. However, the integration of PAK1 into the estrogen response is not fully understood. In this study, we investigated the mechanisms underlying hormone-induced activation of estrogen receptor (ERα, ESR1). We show that estrogen activated PAK1 through both the ERα and GPER1 membrane receptors. Estrogen-dependent activation of PAK1 required the phosphorylation of tyrosine residues by Etk/Bmx and protein kinase A (PKA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
2
26
0
2
Order By: Relevance
“…MCF-7 clones stably overexpressing vector, HA-tagged PAK1 WT and PAK1 Y3F (described in [20]) were maintained in DMEM (Corning Cellgro) supplemented with 10% FBS (Sigma-Aldrich). Deprivation media consisted of DMEM supplemented with 1% bovine serum albumin (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCF-7 clones stably overexpressing vector, HA-tagged PAK1 WT and PAK1 Y3F (described in [20]) were maintained in DMEM (Corning Cellgro) supplemented with 10% FBS (Sigma-Aldrich). Deprivation media consisted of DMEM supplemented with 1% bovine serum albumin (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…In attempt to define the role of PAK1 in the synergistic effect of PRL and estrogen (E2) on breast cancer cell proliferation, we have recently demonstrated that PAK1 phosphorylates Ser305 of estrogen receptor α (ERα) in response to PRL while protein kinase A (PKA) phosphorylates the same site in response to E2 [20]. In this study we provide evidence that PRL activates and promotes PAK1 translocation into the nucleus in ligand- and phospho-tyrosyl-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PAK1 expression is upregulated in prostate cancer, and treatment with the mTOR inhibitor rapamycin slowed cancer cell proliferation by inhibiting PAK1 expression [4]. Furthermore, in human breast cancer cells, PAK1 can mediate cell proliferation and tumor growth, with prolactin treatment triggering PAK1-mediated estrogen receptor-α phosphorylation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Estes mecanismos podem também ser ativados pela prolactina pela ação da proteína JAK (Das e Vonderhaar, 1996;Sato et al, 2013). Além disso, alguns autores sugerem que os dois hormônios poderiam ter ação sinérgica, o que incrementaria a migração celular (Oladimeji et al, 2016).…”
Section: Discussionunclassified
“…Nesse tipo de câncer, a modificação do alinhamento das fibras colágenas (que se tornam mais perpendiculares na superfície da célula) é fator preditivo de sua agressividade (Barcus et al, 2013) que também é alvo da prolactina (Barcus et al, 2015). Possivelmente, a PRL pode ter uma ação sinérgica ao estrogênio na MEC (Oladimeji et al, 2016).…”
Section: Discussionunclassified